Human Vision and Electronic Imaging XX 2015
DOI: 10.1117/12.2086258
|View full text |Cite
|
Sign up to set email alerts
|

The role of natural lighting diffuseness in human visual perception

Abstract: The pattern of the light that falls on the retina is a conflation of real-world sources such as illumination and reflectance. Human observers often contend with the inherent ambiguity of the underlying sources by making assumptions about what real-world sources are most likely. Here we examine whether the visual system's assumptions about illumination match the statistical regularities of the real world. We used a custom-built multidirectional photometer to capture lighting relevant to the shading of Lambertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Although previous studies have showed that natural lighting is often diffuse and directional (Morgenstern, Geisler, & Murray, 2014), we do not yet know how diffuse the lighting priors for the 3-D shape and lightness perceptions are. The diffuseness of assumed lighting has not attracted as much attention as its direction; however, it is also worth investigating (Langer & Bülthoff, 2000;Morgenstern, Geisler, & Murray, 2015;Murray & Adams, 2019;Stone, Kerrigan, & Porrill, 2009;Xia, Pont, & Heynderickx, 2017a, b, c).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have showed that natural lighting is often diffuse and directional (Morgenstern, Geisler, & Murray, 2014), we do not yet know how diffuse the lighting priors for the 3-D shape and lightness perceptions are. The diffuseness of assumed lighting has not attracted as much attention as its direction; however, it is also worth investigating (Langer & Bülthoff, 2000;Morgenstern, Geisler, & Murray, 2015;Murray & Adams, 2019;Stone, Kerrigan, & Porrill, 2009;Xia, Pont, & Heynderickx, 2017a, b, c).…”
Section: Discussionmentioning
confidence: 99%
“…The light field in natural scenes is highly complicated due to intricate optical interactions, containing low and high frequencies in the radiance distribution function. Nonetheless, the human visual system (HVS) is able to distinguish the intensity, the primary illumination direction, and the diffuseness, which are basic (low-order) properties of a light field ( Cuttle, 2003 ; Frandsen, 1989 ; Koenderink, van Doorn, Kappers, Pont, & Todd, 2005 ; Morgenstern, 2011 ; Morgenstern, Geisler, & Murray, 2014 ; Mury, Pont, & Koenderink, 2007 ; O'shea, Agrawala, & Banks, 2010 ; Pentland, 1982 ; Pont, 2013 ; Te Pas & Pont, 2005 ). Mury et al ( Mury, 2009 ) described the relations between the mathematical structure and physical meaning of the light field components, plus a manner to measure and visualize the light field.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have shown that natural lighting is often diffuse and directional ( Morgenstern, Geisler, & Murray, 2014 ), we do not yet know how diffuse the lighting priors for the 3-D shape and lightness perceptions are. The diffuseness of assumed lighting has not attracted as much attention as its direction; however, it is also worth investigating ( Langer & Bülthoff, 2000 ; Morgenstern, Geisler, & Murray, 2015 ; Murray & Adams, 2019 ; Stone, Kerrigan, & Porrill, 2009 ; Xia, Pont, & Heynderickx, 2017a , 2017b , 2017c ).…”
Section: Discussionmentioning
confidence: 99%